2015
DOI: 10.3109/02770903.2015.1070862
|View full text |Cite
|
Sign up to set email alerts
|

Twelve- and 52-week safety of albuterol multidose dry powder inhaler in patients with persistent asthma

Abstract: Objective: Evaluate the safety of albuterol multidose dry powder inhaler (MDPI), a novel, inhalation-driven device that does not require coordination of actuation with inhalation, in patients with persistent asthma. Methods: We report pooled safety data from two 12-week, multicenter, randomized, double-blind, repeat-dose, parallel-group studies and the 12-week double-blind phase of a 52-week multicenter safety study as well as safety data from the 40-week open-label phase of the 52-week safety study. In each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The incidences of severe AEs varied in different indication subgroups and formulation subgroups (Table 1). Compared with COPD subgroup (pooled incidence: 6%, 95% CI : 3%–9%), 66 the risk of severe AEs in asthma subgroup was slightly lower (pooled incidence: 2%, 95% CI : 1%–3%, I 2 = 59.2%, P = 0.004), 26,33,50,77,81 while inhaled salbutamol subgroup (pooled incidence: 2%, 95% CI : 1%–3%, I 2 = 67.6%, P = 0.004) 26,33,50,66,77,81 was with a lower risk of severe AEs than intravenous subgroup (pooled incidence: 6%, 95% CI : 2%–9%, P = 0.038) 73 . No studies reported severe AEs either in premature labour subgroup or oral subgroup.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The incidences of severe AEs varied in different indication subgroups and formulation subgroups (Table 1). Compared with COPD subgroup (pooled incidence: 6%, 95% CI : 3%–9%), 66 the risk of severe AEs in asthma subgroup was slightly lower (pooled incidence: 2%, 95% CI : 1%–3%, I 2 = 59.2%, P = 0.004), 26,33,50,77,81 while inhaled salbutamol subgroup (pooled incidence: 2%, 95% CI : 1%–3%, I 2 = 67.6%, P = 0.004) 26,33,50,66,77,81 was with a lower risk of severe AEs than intravenous subgroup (pooled incidence: 6%, 95% CI : 2%–9%, P = 0.038) 73 . No studies reported severe AEs either in premature labour subgroup or oral subgroup.…”
Section: Resultsmentioning
confidence: 96%
“…Based on the full‐text review, 93 articles were ruled out for one or more of the following reasons: reviews, duplicated cohorts, commentaries, non‐randomized trials, non‐human trials or without AEs outcomes. Ultimately, 58 RCTs with a total of 12 961 patients were included in this meta‐analysis 24–81 . The selection procedure is depicted in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, schools should be allowed to use albuterol in respiratory emergencies, even when a child lacks a documented asthma diagnosis. Albuterol is a safe drug to administer to any child in respiratory distress ( 35 38 ). To obtain stock medication for schools/districts, pharmacy dispensing law(s) should also be addressed.…”
Section: Steps To Pass Stock Albuterol Legislationmentioning
confidence: 99%